Global or Local Identities? How Thai Learners in an English Program Project Themselves through L2 Pronunciation in ELF Encounters - Prakaianurat, Pichet; Kangkun, Preena (LEARN Journal: Language Education and Acquisition Research Network, 2024)
This study combines qualitative and quantitative methods to explore 15 English program (EP) students’ attitudes toward English varieties and how they negotiate social meanings and construct their identity through stylistic practices in classroom discourse and English as a lingua franca (ELF) interactions. Through a verbal guise test, semi-structured interviews, and auditory impression analysis, the results indicated a strong preference for native-based English varieties, with American English linguistic resources being more prevalent in the speech of EP students than those of British English. The findings revealed that in ELF talks all EP students adopted native-like speech styles, which were perceived as more socially prestigious and communicatively advantageous, to indexically construct a “proficient” English speaker identity and establish a sense of in-group global community membership. However, within EP classroom discourse, certain participants demonstrated style-shifting by the local variants of Thai-accented English to project a “Popular” identity, distancing themselves from the “Bookishness” group within the EP community of practice. The study underscores the importance of native-based norms and socially sensitive pedagogical approaches, enabling students to construct their distinct identities through L2 pronunciation while also recognizing the plurality of English varieties present in their particular linguistic landscape.